(3QDhS GdeSGFd GdNdGajI (B( (3Hjf LeghQ GdabgGA jfUQ ajg ePgH CMeO Hf MfHd(B)s - (3CHh GdehGgH GdMSjf Hf eMeO GdYcHQjs
(3ChdgG (B:s
(3jHJOF HcJGH GdgHI s
(3BNQgG (B:s
(3jfJgi HcJGH CegGJ GdChdGO s
(3JHUQI GdYfhGf (B:s
(3JNQjL s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3GNJdGa GdabgGAs